Pembangunan Local Area Network Laboratorium Komputer Madrasah Tsanawiyah Al Huda 1 Karangpandan - S, Ninik Rahmawati (Indonesian Journal of Networking and Security (IJNS), 2013)
Abstrack – Subjects Information and Communication Technology (ICT) is a science that requires a lot of practice to theory in order for students to have expertise in the field of computer science. Achievement of the goals of teaching and learning practices in the subjects of Information Technology and Communication at MTs Al Huda 1 Karangpandan will be determined by the completeness of laboratory facilities. The problems experienced by the junior secondary school computer labs (MTs) Al Huda 1 Karangpandan originated from the limited budget for the laboratory, resulting in lack of laboratory equipment that is not proportional to the number of students. Especially the amount of hardware, namely printers when used for practice and computer print outs when used for practice exams. In practice the exam each student must work individually not as a group. Individual exam is done so that the scoring of each student according to capabilities. With state of the number of printers that are not proportional to the number of students that the exam should be done alternately. Students practice exam results are stored to be used as evidence that the student has followed the trials and also as an archive. In order to test the student's file is not used by students who test on the next turn then this file should be removed before the computer is used to test the next student. With the construction of network of Local Area Network (LAN) is a solution of two problems. With the construction of the laboratory LAN computer can use resources that together with the data sharing and printer sharing. In this study the authors used the following research methods of observation, interviews, library research, analysis, design, preparation, development lan, testing, implementation. Kata Kunci : MTS Al huda 1, Local Area Network, Data sharing   Abstraksi – Mata pelajaran Teknologi Informasi dan Komunikasi (TIK) adalah ilmu yang banyak membutuhkan praktik dari pada teori dengan tujuan agar siswa dapat memiliki keahlian dibidang ilmu komputer. Pencapaian tujuan belajar mengajar praktik pada  mata pelajaran Teknologi Informasi dan Komunikasi di MTs Al Huda 1 Karangpandan akan  ditentukan oleh kelengkapan fasilitas laboratorium. Permasalahan yang dialami oleh laboratorium komputer Madrasah Tsanawiyah (MTs) Al Huda 1 Karangpandan  berawal dari terbatasnya anggaran untuk laboratorium sehingga mengakibatkan minimnya peralatan laboratorium yang tidak sebanding dengan jumlah siswa. Terutama jumlah hardware yaitu printer ketika digunakan untuk praktik print out dan komputer ketika digunakan untuk ujian praktik. Dalam pelaksanaan ujian praktik setiap siswa harus mengerjakan secara individu tidak secara berkelompok. Ujian secara individu ini dilakukan agar pemberian nilai dari masing-masing siswa sesuai dengan kemampuan yang dimiliki. Dengan keadaan jumlah printer yang tidak sebanding dengan jumlah siswa maka ujian harus dilakukan secara bergantian. Hasil ujian praktik siswa ini disimpan untuk digunakan sebagai bukti bahwa siswa tersebut telah mengikuti ujian dan juga sebagai arsip. Agar file ujian siswa ini tidak digunakan oleh siswa yang ujian pada giliran berikutnya maka file ini harus dipindah terlebih dahulu sebelum komputer digunakan untuk ujian siswa yang berikutnya. Dengan dibangunnya jaringan Local Area Network (LAN) adalah satu solusi dari dua permasalahan tersebut. Dengan  dibangunnya LAN maka laboratorium komputer dapat menggunakan sumberdaya secara bersama-sama yaitu dengan sharing data dan sharing printer. Dalam penelitian ini penulis menggunakan metode penelitian sebagai berikut observasi, wawancara, studi pustaka, analisis, perancangan, persiapan, pembangunan lan, testing, implementasi. Kata Kunci : MTS Al huda 1, Local Area Network, Sharing data